FPGA Based Optimized Discontinuous SVPWM Algorithm for Three Phase VSI in AC Drives - Tole Sutikno; Nik Rumzi Nik Idris; Auzani Jidin; Mohd Hatta Jopri (Institute of Advanced Engineering and Science, 2013)
The discontinuous space vector pulse width modulation (SVPWM) has well-known that can reduce switching losses. By simplifying the thermal management issues, the discontinuous SVPWM can potentially reduce the inverter size and cost. However, using the modulation due to different time interval equations for each sector can introduce glitches at the points when the sector is changed. The more main problem, it can increase unwanted harmonic content and current ripple. Consider the decrease in switching losses associated with discontinuous modulation allows the system to utilize a higher switching frequency, this paper present high frequency switching of optimized discontinuous SVPWM based on FPGA to overcome the problems above. The proposed SVPWM has been successfully implemented by using APEX20KE Altera FPGA to drive on a three phase inverter system with 1.5 kW induction machine as load. The results have proved that the method can reduce harmonic content and current ripple without glitches.DOI : http://dx.doi.org/10.11591/ijpeds.v3i1.735